1993
DOI: 10.2472/jsms.42.1445
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Dynamic Interlaminar Fracture Toughness of CFRP by ENF Test Using SHPB Method.

Abstract: To obtain the dynamic Mode II interlaminar fracture toughness of CFRP under impact loading, an impact bend test using split Hopkinson pressure bar (SHPB) method was applied to the end notched flexure (ENF) specimen, and the estimation of GII was investigated. The dynamic behavior of the ENF specimen during impact bending was analysed by the finite element method, and the history of the energy release rate GII of the specimen was calculated using the crack-closure method. The energy release rate GIICC calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Fig.2 represents a ramped incident wave generated by plastic deformation of metallic buffer placed at the impact end of input bar and successful results of transmitted wave without undulations. The method was applied to fracture characterization on several composites materials in various modes 20 . …”
Section: Bending Testmentioning
confidence: 99%
“…Fig.2 represents a ramped incident wave generated by plastic deformation of metallic buffer placed at the impact end of input bar and successful results of transmitted wave without undulations. The method was applied to fracture characterization on several composites materials in various modes 20 . …”
Section: Bending Testmentioning
confidence: 99%
“…Because of this, improvement of interlaminar characteristics is necessary in order to improve the mechanical characteristics of mechanical joints in composite laminates. Although various studies have investigated ways to improve the interlaminar characteristics of composite laminates [5] [6] [7] [8] [9], here we focused on applying needle punching process to the reinforcement of the composite material as means of improving these characteristics. Needle punching process is a fabric processing method that is used to create non-woven fabric and is able to create interlacing of fabrics in the thickness direction by piercing cottony fiber with special barbed needles called felting needles.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, a hydraulic testing machine (loading rates of less than 0.1 m/s) [41, a drop weight testing system (1.25 to 3 m/s) [5,6], and the split Hopkinson pressure bar (SHPB) method (0.2 to 20 m/s) [7][8][9] were utilized in dynamic mode II interlaminar fracture tests. In the instrumented drop weight testing system, it is usually difficult to evaluate the load applied to the specimen accurately because periodic oscillation due to inertial effect and the multiple-reflection of the stress wave is normally observed in the load-time history when the load is measured from strain gages attached to the loading dart [10].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has been shown that it is possible to apply the static analyses to the dynamic testings even at relatively high rates if quasistatic stress states are achieved [7][8][9].…”
mentioning
confidence: 99%